Study of Toxoplasmosis Infection in Human and Related to Animal in Banda Aceh - Hanafiah, Muhammad; Kamaruddin, Mufti; Nurcahyo, Wisnu; Winaruddin, Winaruddin (Universitas Syiah Kuala, 2010)
The research has been done to know prevalence of toxoplasmosis in livestock, to search the source of infection that have potency to cause toxoplasmosis in human and to make a map of toxoplasmosis infection area in Banda Aceh. The method used in this research was serologic test, Card Aglutination Test (CATT). Data of fertile women in this study are collected through questioner. The result of this research showed that the toxoplasmosis prevalency number of society in Banda Aceh was 3.15%, while at livestock were varied respectively: goats 40%, chickens 25%, cattles 23%, duck 20%, cats 16%, buffalos 15%, and sheeps 10%. The potencial sources of to coures toxoplasmosis in human are: goat, chicken, cattle, duck, cat, buffalo, and sheep. The area found toxoplasmosis in humans and animal were: Baiturrahman, Kuta Raja, Ulee Kareng, Kuta Alam, and Syiah Kuala. Model toxoplasmosis infection patterns in human related to livestock and animal in Banda Acheh are : Y ( POSTOKSO) - 1,55688 + 2,65280 AYA + 1,17709 JDG + 4,28482 KUC - 3,74609 MEM